Unlocking Creativity: Exploring the Effects of Physics Modelling on Creative Thinking Skills - Andi Ichsan Mahardika; Muhammad Arifuddin; Devi Munawaroh (Jurnal Pendidikan Progresif, 2024)
Unlocking Creativity: Exploring the Effects of Physics Modelling on Creative Thinking Skills. Objectives: Knowing the improvement of creative thinking skills through the implementation of physics Modelling learning is the purpose of the research conducted. Methods: The research was conducted using Experimental Design method. This research trial used one group pre-test post-test design on 33 high school students and the data were analyzed  using n-gain score test  results and hypothesis test using Wilcoxon's non-parametric statistical test to determine whether there was an average difference between two paired samples. Findings: The results of the analysis showed that the implementation of physics modelling learning can improve creative thinking skills with an n-gain of 0.496 for the fluency aspect, 0.72 for the flexibility aspect, and 0.87 for the originality aspect. Apart from that, there was a significant increase in creative skills between before and after the implementation of physical Modelling learning tested through the non-parametric Wilcoxon test. Conclusion: Thus, it can be concluded that physics Modelling learning can be used as an alternative learning because it is effective and significant for improving creative thinking skills. Keywords: creative skill development, creative thinking skill, physics modelling learning.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202456